ANALISIS MUATAN NOS PADA MATERI LAJU REAKSI DALAM BUKU TEKS KIMIA SMA KELAS XI DI KOTA BANDUNG - Ghalda Hanifah Pratiwi, - (2021)
Understanding of Nature of Science (NOS) is one of characteristic that expected to be have for person who scientific literate. Lack ability to understanding of NOS is become one of factor cause lower student's scientific literate. Textbook is one of teaching materials which often to use in science's learning process. Because of that, this study was conducted to produce information related to balancing of NOS in one of chemistry chapters that is reaction rate in the dominant two chemistry textbooks used by teachers and 11th grade high school students in Bandung city. This study used descriptive research with quantitative research as a research design and content analysis as a method. A protocol procedures developed by Lee (2007) used in this study to obtain the percentage of each aspect that contains NOS in chapter of reaction rate in two textbooks. The results showed that the first dominant textbook contained 50,3% of science as a body knowledge, 34,2% of science as a way of investigation, 11,8% of science as a way of thinking, and 5,3% of interaction between science, technology, and society. While the second textbook contained 50,8% of science as a body knowledge, 25,4% of science as a way of investigation, 16,8% of science as a way of thinking, and 9,6% of interaction between science, technology, and society. It is provide that two chemistry textbooks has not shown the balance of every aspect of NOS.